Impact factor method for design of bridge foundations under ship collisions. Issue 4 (April 2017) - Wang, Junjie; Song, Yanchen; Yu, Zhiran
Due to the complexity involved and limited study on the topic, the equivalent static method, adopted in the current codes for structural design of bridges under ship collisions, does not take into account the dynamic amplification effect correctly. In this article, impact factor method is proposed to estimate the response of bridge's piers and foundations, as a better alternative of the equivalent static method. Through refined numerical simulations of ship-rigid wall collisions for nine typical ships under various impact velocities, 81 impact force time-histories are obtained. The period-dependent impact factor is defined, and empirical function of it is proposed and parameters in the empirical function are determined by the 81 sample impact force time-histories. Finally, both impact factor method and dynamic time-history method are used to estimate the responses of piers and foundations of two example bridges, and the precision of impact factor method is discussed.